The Influence of Price, Product Quality, and Brand Image of Bear Brand Milk on Purchase Decisions during a Pandemic Period for Students of Muhammadiyah University of Sidoarjo Management Study Program - Nur Fauziatin Anisa; Herlinda Maya Kumala Sari (Journal of Islamic and Muhammadiyah Studies, 2022)
This thesis is not published. Faculty of Business, Law and Communication Sciences, University of Muhammadiyah Sidoarjo. The purpose of thispstudy is toodetermine andanalyze the effect of Price, Production Quality, and Brand Image on Bear Brand milk purchasing decisions for students of Management Study Program, Muhammadiyah University of Sidoarjo. This study uses quantitative methods. Data collection techniques using questionnaires, distributed to 100 students Muhammadiyah University of Sidoarjo. The data analysis technique used in this research is non-random sampling using purposive sampling with the help of SPSS (Statistical Program for Social Science) version 25. The results of this study indicate that the price variable has a significant effect on purchasing decisions, the product quality variable has a significant effect on purchasing decisions, brand image has a significant effect on purchasing decisions, and the variables price, product quality, and brand image have a significant effect on purchasing decisions for bear brand milk in college students. Muhammadiyah University of Sidoarjo